Aspectos patológicos e imuno-histoquímicos de neoplasmas em ovinos - Melo, Stella Maris Pereira de (2021)
Neoplasms in sheep are uncommon, and the prevalence of different histological subtypes of tumours can vary widely between different geographic regions. In the literature, there are few characterization studies that investigate the prevalence, and detail the pathological and immunohistochemical aspects of neoplastic diseases in this species. Thus, the objective of this study was to determine the prevalence of neoplasms in sheep at the Veterinary Pathology Laboratory (LPV) of the Federal University of Santa Maria (UFSM), for 40 years (1980-2019), and to characterize its macroscopic, histopathological, and immunohistochemical aspects. Information regarding the profile of the animals (age, breed, and sex), clinical, macroscopic and histological changes were collected from the necropsy reports and histopathological exams with diagnosis of neoplasms. During this period, of a total of 1,945 exams performed, 35 sheep (1.8%) were affected by neoplasms, the majority being classified as malignant (30/35). In general, the most prevalent tumour was squamous cell carcinoma (17/35) and mainly affected the integumentary system (10/17). Other types of neoplasms occurred less frequently, affecting different organ systems and comprised, in decreasing order: lymphoma (7/35), intestinal adenocarcinoma (3/35), fibroma (3/35), hepatocellular carcinoma (1/35), cholangiocarcinoma (1/35), fibrosarcoma (1/35), papilloma (1/35) and ruminal fibropapilloma (1/35). Histologically, neoplasms of epithelial origin were characterized by cubic or polyhedral cells arranged in islands, ribbons, cords, nests, acini or ducts. Tumours of mesenchymal origin or of round cells, presented spindle or round cells arranged in bundles or in mantle. Some histological types, such as cholangiocarcinoma and fibrosarcoma, showed particularly unusual macroscopic and histological changes in this case series. The immunohistochemistry technique was performed mainly on malignant tumours and allowed to determine the origin of the neoplastic cells in some cases, which helped to confirm the diagnosis. Through this study, it was possible to know the prevalence of neoplasms in sheep in the routine of a veterinary pathology laboratory in 40 years of diagnosis. The study also made it possible to characterize the anatomopathological and immunohistochemical aspects of these neoplasms, providing new and relevant information for the diagnosis of neoplasms in the sheep species.